Characterisation, whole‐genome sequencing and phylogenetic analysis of three H3N2 avian influenza viruses isolated from domestic ducks at live poultry markets of Iran, 2017: First report - Alireza Abtin; Abdelhamid Shoushtari; Mohammad Hossein Fallah Mehrabadi; Aidin Molouki; Seyed Ali Pourbakhsh; Hadi Pourtaghi; Fatemeh Eshratabadi (Veterinary Medicine and Science, 2022)
Abstract Background Avian influenza type A viruses (AIV) can infect a broad range of hosts including human and birds, making them an important viral pathogen with zoonotic potential. Ducks are a known reservoir for many avian viruses including the AIV. Objectives To sequence the entire genome of duck‐derived H3N2 and ran comprehensive phylogenetic analysis on them to study their origin. Methods In this study, 962 cloacal swabs were collected from domestic ducks at several live poultry markets (LPMs) of Gilan, Mazandaran and Golestan provinces of Iran in the year 2017. Results Preliminary assays such as haemagglutination inhibition assay (HI), Neuraminidase Inhibition assay(NI) and RT‐qPCR suggested that 0.5% of the birds were infected by H3 low pathogenic influenza viruses (LPAI). Three isolates were selected for whole genome sequencing. The cleavage site of the HA genes showed a PEKQTR/GLF motif, an indicator of LPAI. Furthermore, BLAST and phylogenetic analyses of the HA gene showed high homology to the Eurasian lineage of H3N8 AIV (95.5%–97.1% to several European and East Asian isolates). However, the NA genes showed high homology (at most 96.5–96.9%) to those belonging to AIV N2 subtype. Furthermore, internal genes showed high homology (96%–98%) to a variety of duck‐origin subtypes and glycoprotein combinations, which were different for each segment. This showed a complex reassortment between different subtypes. Discussion This report is the first whole genome sequencing and complete characterisation of H3N2 AIV from Iran. Conclusion Such surveillance should continue to study the evolution and possible emergence of viruses with pandemic potential.